Influência do exercício físico sobre parâmetros de comportamento e estresse oxidativo em modelo animal de discinesia tardia - Teixeira, Angelica Martelli (2008)
Regular practice of physical activity promotes beneficial effects to the body. However, excessive duration and intensity of exercise may surpass individual tolerance to exercise, generating oxidative stress (OS). Studies have shown these effects in various organs, such as the heart and muscles, but little is known about their action and mechanisms in the brain. Various neurological and neurodegenerative diseases are associated with OS and neurotoxicity. Considering these aspects, the first objective of this study was to determine the influence of chronic moderate exercise in an OS model induced by reserpine in rats. The animals were submitted to daily sessions of swimming, with a gradual increase in the length of training. After eight weeks, the animals received two injections of reserpine or control solutions (1 mg/kg-sc), alternately. A behavioral evaluation was performed, after which the rats were euthanized and the striatum was dissected for enzymatic and biochemical assays. Reserpine increased the vacuous chewing movements frequency (VCM) and facial twitching (FT), as well as catalase activity, but decreased reduced glutathione levels (GSH). Exercise partially prevented FT, and partially recovered GSH levels, but did not modify the effects on catalase and VCM. There was a positive correlation between catalase activity and orofacial dyskinesia (OD) and a negative correlation between GSH and OD. The second objective of this study was to evaluate the effects of an intense physical activity in the same model of OS. Rats were submitted to eleven weeks of swimming (1 h/day), where each rat s load was increased according to its body weight until reaching 7% of its weight. Behavioral evaluations were performed before euthanasia and the striatum was then dissected for assays. The effectiveness of the training was confirmed through reduced levels of serum lactate and cardiac hypertrophy, observed in exercised animals. Intense exercise reduced the locomotor index and exploratory activity of the animals, demonstrating the development of emotional stress. In the presence of reserpine, exercise increased lipid peroxidation (TBARS) and caused an increase in catalase activity, which were positively correlated with each other. Based on the results, it was concluded that chronic physical activity of moderate intensity improved the antioxidant defenses in movement disorders associated with cerebral OS. On the other hand, excessive exercise caused negative emotional disorders and, in the presence of another aggressor agent, modified brain antioxidant capacity, which possibly could aggravate cases of neurological and/or neurodegenerative diseases associated with oxidative processes.